Fabrication and characterization of the blend of Polyurethane (PU) and Phase Change Materials (PCM) for energy storage and release. (21st July 2020) - Tariq, Asra; Shakir, M Fayzan; Afzal, Ayesha; Abdul Rashid, Iqra; Iqbal, M Azfar; Rauf, Ammar
Abstract: Utilizing thermal energy storage (TES) system having phase change material (PCM) in it is an effective technique for energy conservation and reduction in greenhouse gas (GHG) emission. Fatty acids have the highest energy storage capacity and easy to process in comparison to all other PCM. Eutectic mixture of palmitic acid (PA) and capric acid (CA) was prepared and thermal analysis was done to confirm its latent heat storage capacity for energy storage and release. This eutectic mixture of fatty acids was physically blended in PMMA to avoid leakage. Fatty acid blended PMMA (F-PMMA) was blended with polyurethane (PU) foam. 10% F-PMMA added as an additive in PU offered highest compressive strength with improved energy absorption.